The Kangâmiut dykes in West Greenland: markers of the tectono-metamorphic evolution of the southern Nagssugtoqidian orogen and its foreland - Korstgård, John; Mengel, Flemming; Glassley, William; Sørensen, Kai (Geological Survey of Denmark and Greenland (GEUS), 2024)
The general extent and structural evolution of the southern Nagssugtoqidian orogen of West Greenland were first described by Hans Ramberg who based much of his paper on the deformation of the regional Kangâmiut dyke swarm. The southern boundary is marked by a transition from undeformed, discordant dykes in the south to highly deformed dykes and host rocks to the north. Our analysis of the southern Nagssugtoqidian orogen and its southern foreland uses a comprehensive compilation of available data and covers the area from Sisimiut in the north to Alanngua, south of Maniitsoq. This represents almost the entire c. 200 km latitudinal extent of the Kangâmiut dyke swarm and encompasses the complete range of Nagssugtoqidian overprint on these dykes and their country rocks. South of Itillip Ilua (Itilleq), the structural and metamorphic overprints on the dykes exhibit a considerable range in both intensity and P–T conditions between and even within outcrops. In contrast, north of Itillip Ilua, the rocks show more systematic gradual increases in the degree of structural overprints and metamorphic grade, culminating in the Ikertooq thrust zone where granulite facies rocks are brought southwards over amphibolite facies rocks. Currently, available age data from the Nagssugtoqidian orogen permits the identification of two metamorphic episodes at c. 1850–1800 Ma and c. 1780–1720 Ma. These groups of metamorphic ages are supported by recent 40Ar–39Ar ages from dykes in the same area, which cluster at c. 1860 Ma and c. 1740 Ma, respectively. Albeit geographically sporadic, both age intervals support a subdivision of the Nagssugtoqidian structural and metamorphic overprints across the southern Nagssugtoqidian orogen and its foreland into two distinguishable temporal phases. Further geochronological investigations may well, however, find these two phases to be part of a tectonic continuum. For now, it is thought that the older event records south-directed thrusting over the foreland and concomitant loading of this crust, at least ...